ISOLASI DAN KARAKTERISASI KAPANG ENDOFIT DARI PEGAGAN (Centella asiatica (L.) URBAN) - Nur Sabrina Hasyyati; Agung Suprihadi; Budi Raharjo; Kristiani Dwiatmi (Jurnal Akademika Biologi, 2017)
Endophytic mold live in colonies in healthy plant tissues without causing damage to the host plant. Various types of plants can be potentially as a source of endophytic mold isolates. Plants that are hosts for the mold endophyte one of them is gotu kola (Centella asiatica (L.) Urban). This study aimed to isolate and identify the molecular of endophytic molds from gotu kola. Isolation of endophytic mold through the stages namely stage surface sterilization and purification. Mold isolates obtained later in the identification of the molecular basis using ITS region. DNA amplification using the primers ITS ITS 4 and 5. Ribbon successfully amplified DNA with a size of 600 bp. The results of molecular identification and phylogenetic analysis based BLAST. The results of the analysis of BLAST showed similarities each - each isolates with species of mold on genebank known isolates BiogenCC M1 and BiogenCC M25 with Phoma sp., Isolate BiogenCC M6 with    Colletotrichum siamense, isolates BiogenCC M10 is Colletotrichum destructivum, isolates BiogenCC M15 and BiogenCC M28 with Mycoleptodiscus indiscus, and isolates BiogenCC BiogenCC M18 and M19 with Fusarium oxyporum. Keywords: Mold endophyte, Moleculer identification, ITS, Pegagan.